Castles - Baines, Francesca; Bergin, Mark (New York : F. Watts, 1995)
Explains how castles were built and describes the lifestyles of the people who lived in them.
Includes index.
4.6
3-6
Keywords: Castles -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Castles; Civilization, Medieval; Castles; Medieval civilization